2023
DOI: 10.1111/bjet.13298
|View full text |Cite
|
Sign up to set email alerts
|

Video demonstrations can predict the intention to use digital learning technologies

Abstract: The technology acceptance model (TAM) uses perceived usefulness and perceived ease of use to predict the intention to use a technology which is important when deciding to invest in a technology. Its extension for e-learning (the general extended technology acceptance model for e-learning; GETAMEL) adds subjective norm to predict the intention to use. Technology acceptance is typically measured after the technology has been used for at least three months. This study aims to identify whether a minimal amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Likewise, behavioral intention can also be influenced by outside variables such as task technological fit, societal effect, and enabling conditions (Ishfaq & Mengxing, 2021). Behavioral intention toward technology is measured by the Technology Acceptance Model (TAM) with perceived usefulness and perceived ease of use to predict the intention to use a technology which is important when deciding to invest in a technology (Sprenger & Schwaninger, 2023). The creation of the TAM by Davis in 1989 marked the beginning of the study of technology adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, behavioral intention can also be influenced by outside variables such as task technological fit, societal effect, and enabling conditions (Ishfaq & Mengxing, 2021). Behavioral intention toward technology is measured by the Technology Acceptance Model (TAM) with perceived usefulness and perceived ease of use to predict the intention to use a technology which is important when deciding to invest in a technology (Sprenger & Schwaninger, 2023). The creation of the TAM by Davis in 1989 marked the beginning of the study of technology adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This video helped demonstrate the prospect, usage, and interaction mechanism of the proposed AMC for executing different computing tasks to the respondents of the survey. Although familiarizing the users with the proposed AMC in this manner represents a notable limitation of our study, evidence of such an approach to TAM analysis can be found in the literature as well [87,88].…”
Section: Plos Onementioning
confidence: 99%